2021
DOI: 10.1080/10837450.2021.1871918
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and stability study of hydroxychloroquine sulfate oral suspensions

Abstract: Hydroxychloroquine is an antimalarial drug indicated in the treatment of acute attacks of malaria due to Plasmodium vivax, P. malariae, P. ovale, and susceptible strains of P. falciparum. It is also used for the treatment of rheumatoid arthritis, discoid and systemic lupus erythematosus, and more recently proposed in COVID-19 therapy. Hydroxychloroquine is only available in tablets which are not easy to administer for pediatric and geriatric patients, and patients unable to swallow such as patients found in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…An international study including 7,500 physicians from 30 countries has shown that most of the physicians questioned considered hydroxychloroquine (HCQ) the most effective treatment for COVID-19. [8,9] In vitro studies have shown that HCQ sulfate can indeed inhibit SARS-CoV-2 infection, [10,11] while a separate in vitro study reported that the combination of azithromycin and HCQ inhibited SARS-CoV-2 infection. [12] Although the efficacy of this treatment has been accepted, especially when it is started in the early stages of the disease, the efficacy of early treatment has not been investigated in the geriatric population with high mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…An international study including 7,500 physicians from 30 countries has shown that most of the physicians questioned considered hydroxychloroquine (HCQ) the most effective treatment for COVID-19. [8,9] In vitro studies have shown that HCQ sulfate can indeed inhibit SARS-CoV-2 infection, [10,11] while a separate in vitro study reported that the combination of azithromycin and HCQ inhibited SARS-CoV-2 infection. [12] Although the efficacy of this treatment has been accepted, especially when it is started in the early stages of the disease, the efficacy of early treatment has not been investigated in the geriatric population with high mortality rates.…”
Section: Introductionmentioning
confidence: 99%